Census of State and Federal Adult Correctional Facilities, 1995 ([Verlag nicht ermittelbar], 1998)
This census is the fifth enumeration of state adult correctional institutions and the second of federal institutions sponsored by the Bureau of Justice Statistics and conducted by the Bureau of the Census. Earlier censuses were completed in 1974 (ICPSR 7811), 1979 (ICPSR 7852), 1984 (ICPSR 8444), and 1990 (ICPSR 9908). Unlike the previous censuses, all respondents in 1995 were sent the same survey form. For each facility, information was provided on physical security, age, functions, capacity, court orders for specific conditions, one-day counts and average populations, race/ethnicity of inmates, inmate work assignments, inmate deaths, special inmate counts, assaults, and incidents caused by inmates.